UJI CEMARAN BAKTERI COLIFORM PADA MINUMAN AIR TEBU - Yullia Sukawaty; Muhammad Kamil; Eko Kusumawati (Jurnal Ilmiah Manuntung, 2016)
Sugarcane juice beverage is a beverage that is found along the village Sempaja and Pelita roads. Contamination in processed beverages derived from sugarcane juice and equipment used allow for contamination by coliform bacteria. The purpose of this study to investigate the contamination of coliform bacteria in water beverage sugar circulating in the village Sempaja and Pelita. Tests using the Most Probable Number (MPN) includes test estimators using lactose broth as the presumptive medium and Brillian Green Lactose Bile Broth as the confirmad medium. The results showed that eight samples tested positive for coliform contaminated with a high of 2800×101 MPN / mL (sample H) and the lowest value 170×101 MPN/mL (sample D). The results obtained show that the sugarcane juice drinks that supply does not meet the standards of Rule Head POM HK.00.06.1.52.4011 No. 2009 with standard quality requirements of 2×101colonies/mL.